Associated factors with jaundice requiring phototherapy: a case-control study in a hospital in Peru: Factores asociados a ictericia con requerimiento de fototerapia: estudio de tipo casos y controles en un hospital de Perú - Huambo Panduro, Mary Claudia (2024)
Objective: To determine the factors associated with jaundice requiring phototherapy. Material and Methods: An observational, analytical, and retrospective case-control study was conducted. Medical records of 212 patients aged 0 to 7 days from the neonatology service at Hospital Carlos Lanfranco La Hoz were reviewed, divided into 106 cases (with phototherapy) and 106 controls (without phototherapy). Results: Preterm neonates showed a significant association with an OR: 5.526; 95% CI (2.038-14.981), P= 0.001; and ABO incompatibility had an OR: 4.373, 95% CI (1.934-9.889), P= 0.001. However, birth weight, Rh incompatibility, neonatal sepsis, maternal urinary tract infection, and maternal anemia were not associated with the need for phototherapy. Conclusions: There is an association between preterm neonates and ABO incompatibility with the requirement for phototherapy.